John Adair's 100 greatest ideas for amazing creativity - Adair, John Eric, 1934- (West Sussex, United Kingdom : Capstone Publishing Ltd., 2011)
"The final instalment in a new series offering straightforward, practical wisdom from a top business guru John Adair's 100 Greatest Ideas for Amazing Creativity is the second title in a new series of titles from the noted business expert. Focused on concise, practical, and straightforward business wisdom, the series offers the kind of real-world insight that business leaders thrive on. Short, punchy, and packed with real solutions, this book provides 100 proven and effective ideas for businesspeople in need of fresh new ideas, whether they work for a small firm or a Fortune 100 giant. Proven, practical business wisdom for anyone who must create to succeed The second book in a new series from renowned business authority John Adair Quick bites of business wisdom for everyday business success For effective tips on creative thinking from a proven expert, John Adair's 100 Greatest Ideas for Amazing Creativity offers everything you need to invent your own success in business"--
Includes index.
College Students
Keywords: Creative ability in business; Creative thinking; Success in business